A Preliminary Note on Mycorrhiza formation in Chir Pine on Sand at Different N, P, K Levels - Kumar, Dinesh; Singh, Sujan; Thapar, H. S.; Misra, B. M. (Indian Forester, 1968)
Effect of different levels of N, P, & K on mycorrhizal development in 7 month old chir pine seedlings raised on acid washed sand was determined. Inoculations were done with active and washed mycorrhizal roots when seedlings were two months old. Best results were obtained in Â½ normal NPK (corresponding to 65 ppm N & P and 19.5 ppm K). Infection was good in Â¼ normal NPK and in treatments containing N, K (normal) but without P and moderate in 2 normal P &in treatment where N was absent. Variations in dry weights of seedlings in different treatments were not statistically significant. Mycorrhizal fungi were generally active in inoculum or on roots of seedlings as ectotrophic growth or both throughout the experiment. Experiments were conducted on sand culture so that these results may provide a supporting base for further nursery bed experiments to prescribe an optimum fertilizer dosage for both mycorrhiza and the host plant.